2013
DOI: 10.1021/jp309550y
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Partitioning During Colloidal Crystallization

Abstract: We have found that an impurity partitioning takes place during growth of colloidal crystals, which was recognized by the fact that the impurity concentration in the solid (CS) was different from that in the initial solution (C0). The effective partition coefficient k(eff) (=CS/C0) was investigated for pure polystyrene and polystyrene dyed with fluorescent particles by changing the ratio of particle diameters d(imp)/d(cryst) and growth rate V. At each size ratio for the polystyrene impurity, k(eff) was less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Remaining seeds then are either distributed throughout the sample or populate the grain boundaries of the emerging crystals. Their accumulation there is assisted by annealing processes [81,365] and a foam-like microstructure appears similar to that observed for long lasting annealing of AS crystals [298,299]. Cleaning of contaminated crystals can be achieved by processes analogous to zone melting [366].…”
Section: Heterogeneous Nucleationmentioning
confidence: 80%
“…Remaining seeds then are either distributed throughout the sample or populate the grain boundaries of the emerging crystals. Their accumulation there is assisted by annealing processes [81,365] and a foam-like microstructure appears similar to that observed for long lasting annealing of AS crystals [298,299]. Cleaning of contaminated crystals can be achieved by processes analogous to zone melting [366].…”
Section: Heterogeneous Nucleationmentioning
confidence: 80%
“…Nucleation needs seconds to minutes [29], growth needs some minutes to a few hours for completing the phase transformations [14,30]. Coarsening occurs within a few days at room temperature [31,32]. These highly correlated systems become widely recognized as model systems for condensed matter physics.…”
Section: Ducting Materials If the Eriences A Timementioning
confidence: 99%
“…We have already reported that the impurity particles were excluded from the crystals to the grain boundaries during grain growth in charged colloids 10 . Nozawa et al have studied the impurity distribution in charged colloids based on the crystallization theory 33 . A similar exclusion behavior was observed for the present crystallization ( Fig.…”
Section: Resultsmentioning
confidence: 99%